Lubok neun - Ruckhäberle, Christoph; Siemon, Thomas (Leipzig : Lubok Verlag, 2010)
Featuring black and white linocuts by: Julia Weck, Katharina Schilling, Markus Liehr, Mirjam Jacob, Petra Polli, Marie Carolin Knoth, Martin Gross, Robert Brambora, Thomas Stephanblome, Patrick Eicke, Monika Gary-Krug, Tino Geiss, Sebastiann Speckmann, Benjamin DittrichJens Schubert, Julika Achtzig, Anja Triestram, Annika Kleist, Uta Zeidler, Anna Schmocker, Agnes Lammert, Jannine Koch, Karoline Schneider, Claus Stabe, Carolin Schreier, Franziska Neuhofer, Tino Geiss, Berit Mücke, Mandy Kunze, Patrick Fauck, Rebekka Gnädinger, Philipp Orlowski, Rahel Pötsch, Robert Schwark, David Röder.
Exemplar No.: 112/700
boek